Protein kinase C beta II upregulates intercellular adhesion molecule-1 via mitochondrial activation in cultured endothelial cells - Joo, Hee Kyoung (Korean J Physiol Pharmacol, 2017)
Activation of protein kinase C (PKC) is closely linked with endothelial dysfunction. However, the effect of PKCβII on endothelial dysfunction has not been characterized in cultured endothelial cells. Here, using adenoviral PKCβII gene transfer and pharmacological inhibitors, the role of PKCβII on endothelial dysfucntion was investigated in cultured endothelial cells. Phorbol 12-myristate 13-acetate (PMA) increased reactive oxygen species (ROS), p66shc phosphorylation, intracellular adhesion molecule-1, and monocyte adhesion, which were inhibited by PKCβi (10 nM), a selective inhibitor of PKCβII. PMA increased the phosphorylation of CREB and manganese superoxide dismutase (MnSOD), which were also inhibited by PKCβi. Gene silencing of CREB inhibited PMA-induced MnSOD expression, suggesting that CREB plays a key role in MnSOD expression. Gene silencing of PKCβII inhibited PMA-induced mitochondrial ROS, MnSOD, and ICAM-1 expression. In contrast, overexpression of PKCβII using adenoviral PKCβII increased mitochondrial ROS, MnSOD, ICAM-1, and p66shc phosphorylation in cultured endothelial cells. Finally, PKCβII-induced ICAM-1 expression was inhibited by Mito-TEMPO, a mitochondrial ROS scavenger, suggesting the involvement of mitochondrial ROS in PKC-induced vascular inflammation. Taken together, the results suggest that PKCβII plays an important role in PMA-induced endothelial dysfunction, and that the inhibition of PKCβII-dependent p66shc signaling acts as a therapeutic target for vascular inflammatory diseases.